Freiberg’s Infraction in the Context of Systemic Lupus Erythematosus - Bulut Gökten, Dilara; Mercan, Rıdvan (Brazilian Journal of Case Reports, 2024)
Freiberg disease is a rare but clinically significant form of osteonecrosis that can affect the heads of all metatarsal bones, with a particular tendency to involve the second metatarsal. This disease was first identified in 1914, when Alfred Freiberg reported cases of infraction in the second metatarsal head. Several mechanisms have been proposed to explain the cause of the disease, with the most widely accepted being microtrauma, vascular insufficiency, and systemic diseases. Systemic lupus erythematosus (SLE), diabetes mellitus and hypercoagulability are the diseases most frequently cited as contributing to Freiberg’s disease. This report discussed two female patients diagnosed with SLE and presented with pain and swelling in feet, following clinical examination and radiographic evaluation, the patients were diagnosed with Freiberg disease. An orthopedist was consulted, and a multidisciplinary treatment approach was prescribed. Among the osteonecroses associated with SLE, no studies specifically addressing Freiberg’s disease have been found in the literature. This case differs from those in the literature as it specifically describes Freiberg infarction in two patients diagnosed with SLE. This rare condition can complicate the course of systemic diseases and diminish patients’ quality of life. Early recognition by clinicians and ongoing monitoring may help slow disease progression.